Time course and prognostic value of serum GFAP, pNFH, and S100β concentrations in dogs with complete spinal cord injury because of intervertebral disc extrusion. (13th February 2019) - Olby, Natasha J.; Lim, Ji‐Hey; Wagner, Nikki; Zidan, Natalia; Early, Peter J.; Mariani, Christopher L.; Muñana, Karen R.; Laber, Eric
Abstract : Background: A noninvasive biomarker is needed to predict recovery from severe spinal cord injury (SCI) because of thoracolumbar intervertebral disc extrusion (TL‐IVDE). Proteins released from neural and glial cells can be detected in the blood and show promise as prognostic tools, but their concentration is influenced by time after injury. Hypothesis/Objectives: Serum concentrations of glial fibrillary acidic protein (GFAP), phosphorylated neurofilament heavy chain (pNFH), and S100β will follow different time courses; measurement of combinations of these proteins will predict outcome. Animals: Thirty‐one dogs with TL‐IVDE causing paralysis with no pain perception. Methods: Prospective study. Serum samples were taken at presentation and intervals over 56 days and banked at −80°C. Glial fibrillary acidic protein, pNFH, and S100β concentrations were measured using ELISA tests and plotted against time from onset of nonambulatory status. Outcome was established at 6 months. The association between biomarker concentration and outcome was examined using logistic regression, receiver operator characteristics curve analysis, and model development. Results: Thirty‐one dogs participated, 3/31 (10%) developed progressive myelomalacia and 19/31 (62%) recovered ambulation. Glial fibrillary acidic protein and S100β concentrations rose for the first 1 to 3 days, and were undetectable by 14 and 28 days, respectively. Phosphorylated neurofilament heavy chain concentrations peaked at 14 days and were detectable at 56 days. Glial fibrillary acidic protein concentrations in the first 72 hours after onset of nonambulatory status predicted recovery with an accuracy of 76.7%‐89% depending on sample timing. Conclusions and Clinical Importance: Serum GFAP concentrations can be used to predict outcome in clinically complete SCI. A rapid inexpensive bedside test is needed.